Pursuing Urban Commons: Politics and Alliances in Community Land Trust Activism in East London. Issue 1 (17th June 2015) - Bunce, Susannah
Abstract: Community land trust (CLT) practices contribute to analyses of the commons in both conceptual and on‐the‐ground ways. As collective action organizations, CLTs emphasize common land stewardship and resist traditional land speculation and development practices through the mitigation or halting of land value inflation. This paper traces the activist efforts of the East London CLT organization, one of Britain's first urban CLTs, in securing common land in the East London borough of Tower Hamlets, and examines their navigation of political decisions and creation of alliances. Although this process has been challenging as a result of neoliberal governance and private development interests, the East London CLT's trajectory demonstrates the frustrations of activism within these contexts but also the small successes in the pursuit and establishment of urban commons.